2020
DOI: 10.3390/cancers12082141
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin–Resveratrol Combination for Prostate Cancer Management in TRAMP Mice

Abstract: Prostate Cancer (PCa) is a leading cause of cancer-related morbidity and mortality in men. Therefore, novel mechanistically-driven approaches are needed for PCa management. Here, we determined the effects of grape antioxidants quercetin and/or resveratrol (60 and 600 mg/kg, respectively, in diet) against PCa in Transgenic Adenocarcinoma of Mouse Prostate (TRAMP)-model in prevention and intervention settings. We found resveratrol alone and in combination significantly inhibited prostate tumorigenesis in prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 61 publications
0
25
0
2
Order By: Relevance
“…In a very recent study from our lab, we evaluated the effect of quercetin and resveratrol combination in the diet in transgenic adenocarcinoma of the mouse prostate (TRAMP) and have found significant inhibition in PCa development and progression. This is a promising observation; however, this study did not evaluate to assess the level of Zn in response to quercetin and resveratrol combination [103]. These anti-cancer abilities of quercetin along with its ability to increase Zn uptake in the cells indicate that quercetin should continue to be studied for its applications in human PCa.…”
Section: Quercetinmentioning
confidence: 94%
See 2 more Smart Citations
“…In a very recent study from our lab, we evaluated the effect of quercetin and resveratrol combination in the diet in transgenic adenocarcinoma of the mouse prostate (TRAMP) and have found significant inhibition in PCa development and progression. This is a promising observation; however, this study did not evaluate to assess the level of Zn in response to quercetin and resveratrol combination [103]. These anti-cancer abilities of quercetin along with its ability to increase Zn uptake in the cells indicate that quercetin should continue to be studied for its applications in human PCa.…”
Section: Quercetinmentioning
confidence: 94%
“…Resveratrol's effects against cancers including its ability to inhibit key signaling events associated with tumor development and progression, and multidrug resistance, make it is a unique natural agent in cancer management [99,100]. Recent studies on resveratrol alone or combination were shown to have promising anticancer effects against PCa [101][102][103]. However, most of these studies have not evaluated the effect of resveratrol on prostatic Zn levels.…”
Section: Resveratrolmentioning
confidence: 99%
See 1 more Smart Citation
“…Ye et al [ 207 ] and Wang et al [ 208 ] reported that resveratrol suppresses the proliferation of prostate cancer cells, promotes apoptosis, and inhibits the expression of androgen receptors. In vivo studies [ 209 , 210 ] demonstrated that a combination of curcumin and resveratrol exhibited strong modulatory potential against prostate carcinogenesis, while a combination of quercetin and resveratrol may serve as a potential novel regimen for the prevention and/or treatment of prostate cancer.…”
Section: The Role Of Nutritional Factors and Foodstuffs On Prostatmentioning
confidence: 99%
“…Protein from tumor tissues was isolated in 1X RIPA lysis buffer (Millipore), and quantified using Pierce BCA Protein assay kit (Thermo Scientific) as described earlier (25). Wes ProteinSimple, a capillary-based immunodetection system was used for protein analysis.…”
Section: Quantitative Immunodetection Analysis Using Proteinsimplementioning
confidence: 99%